Understanding Judicial Decision-Making: The Importance of Constraints on Non-Rational Deliberations - John N. Drobak; Douglass C. North (Washington University Journal of Law & Policy, 2008)
All of social science is based on the assumption that people act rationally, in a logical, unemotional fashion. This is true for all disciplines in social science, including both economics and law. Neoclassical price theory assumes that producers and consumers are rational actors, while the reasonable person in law is the rational cousin to the economic actor. New institutional economists were among the first scholars to examine economic issues by modifying rational choice theory. Today, a large and growing body of scholarship exhibits a willingness to modify the rationality assumption by using cognitive science, behavioral psychology, and experimental economics. This Essay shares that perspective. In the Essay, we reexamine the way judges make decisions by using contemporary theories from cognitive science and concepts from the new institutional economics.
Keywords: Institutional economics; Judicial discretion; Judicial process -- Research; Public choice theory; Judicial process; Rational choice theory; United States